What Determines Social Behavior? Investigating the Role of Emotions, Self-Centered Motives, and Social Norms - Susanne Leiberg (Frontiers Research Topics, 2016)
Human behavior and decision making is subject to social and motivational influences such as emotions, norms and self/other regarding preferences. The identification of the neural and psychological mechanisms underlying these factors is a central issue in psychology, behavioral economics and social neuroscience, with important clinical, social, and even political implications. However, despite a continuously growing interest from the scientific community, the processes underlying these factors, as well as their ontogenetic and phylogenetic development, have so far remained elusive. In this Research Topic we collect articles that provide challenging insights and stimulate a fruitful controversy on the question of "what determines social behavior". Indeed, over the last decades, research has shown that introducing a social context to otherwise abstract tasks has diverse effects on social behavior. On the one hand, it may induce individuals to act irrationally, for instance to refuse money, but on the other hand it improves individuals' reasoning, in that formerly difficult abstract problems can be easily solved. These lines of research led to distinct (although not necessarily mutually exclusive) models for socially-driven behavioral changes. For instance, a popular theoretical framework interprets human behavior as a result of a conflict between cognition and emotion, with the cognitive system promoting self-interested choices, and the emotional system (triggered by the social context) operating against them. Other theories favor social norms and deontic heuristics in biasing human reasoning and encouraging choices that are sometimes in conflict with one's interest. Few studies attempted to disentangle between these (as well as other) models. As a consequence, although insightful results arise from specific domains/tasks, a comprehensive theoretical framework is still missing. Furthermore, studies employing neuroimaging techniques have begun to shed some light on the neural substrates involved in social behavior, implicating consistently (although not exclusively) portions of the limbic system, the insular and the prefrontal cortex. In this context, a challenge for present research lies not only in further mapping the brain structures implicated in social behavior, or in describing in detail the functional interaction between these structures, but in showing how the implicated networks relate to different theoretical models. This is Research Topic hosted by members of the Swiss National Center of Competence in Research "Affective Sciences - Emotions in Individual Behaviour and Social Processes". We collected contributions from the international community which extended the current knowledge about the psychological and neural structures underlying social behavior and decision making. In particular, we encouraged submissions from investigators arising from different domains (psychology, behavioral economics, affective sciences, etc.) implementing different techniques (behavior, electrophysiology, neuroimaging, brain stimulations) on different populations (neurotypical adults, children, brain damaged or psychiatric patients, etc.). Animal studies are also included, as the data reported are of high comparative value. Finally, we also welcomed submissions of meta-analytical articles, mini-reviews and perspective papers which offer provocative and insightful interpretations of the recent literature in the field.